Native Lizards Living in Brazilian Cities: Effects of Developmental Environments on Thermal Sensitivity and Morpho-Functional Associations of Locomotion - Rossigalli-Costa, Nathalia; Kohlsdorf, Tiana (Frontiers in Physiology, 2022)
Environmental conditions often affect developmental processes and consequently influence the range of phenotypic variation expressed at population level. Expansion of urban sites poses new challenges for native species, as urbanization usually affects the intensity of solar exposure and shade availability, determining the thermal regimes organisms are exposed to. In this study, we evaluate the effects of different developmental conditions in a Tropidurus lizard commonly found in Brazilian urban sites. After incubating embryos of Tropidurus catalanensis in two different thermal regimes (Developmental Environments [DE]: cold = 24oC and warm = 30oC), we measured morphological traits in the neonates and quantified locomotor performance in horizontal and vertical surfaces at three temperatures (Test Temperatures [TT] = 24oC, 30oC and 36oC). Results indicate effects of developmental temperatures on morphological features, expressing functional implications that might be decisive for the viability of T. catalanensis in urbanized areas. Lizards ran similarly on horizontal and vertical surfaces, and isolated analyses did not identify significant effects of DE or TT on the sprint speeds measured. Absolute Vmax (i.e. the maximum sprint speed reached among all TTs) positively correlated with body size (SVL), and neonates from the warm DE (30°C) were larger than those from the cold DE (24°C). Morpho-functional associations of absolute Vmax also involved pelvic girdle width and forelimb, hindlimb, trunk, and tail lengths. Emerging discussions aim to understand how animals cope with abrupt environmental shifts, a likely common challenge in urbanized sites. Our findings add a new dimension to the topic, providing evidence that temperature, an environmental parameter often affected by urbanization, influences the thermal sensitivity of locomotion and the morphological profile of T. catalanensis neonates. Thermal sensitivity of specific developmental processes may influence the ability of these lizards to remain in habitats that change fast, as those suffering rapid urbanization due to city growth.